2014
DOI: 10.2337/db13-0537
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells From Visceral Adipose Tissue Disrupt Adipocyte Functions in a Three-Dimensional Setting: Partial Rescue by Angiopoietin-1

Abstract: During obesity, chronic inflammation of human white adipose tissue (WAT) is associated with metabolic and vascular alterations. Endothelial cells from visceral WAT (VAT-ECs) exhibit a proinflammatory and senescent phenotype and could alter adipocyte functions. We aimed to determine the contribution of VAT-ECs to adipocyte dysfunction related to inflammation and to rescue these alterations by antiinflammatory strategies. We developed an original three-dimensional setting allowing maintenance of unilocular adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 48 publications
1
44
0
Order By: Relevance
“…15, 16 ECs of inflamed adipose tissue from obese subjects have adverse effects on insulin signaling in adipocytes such as reduced expression of phospho-Akt at Ser473, increased endoplasmic reticulum stress, and release of inflammatory mediators. 17 On the other hand, EC function is subjected to the regulation by insulin-mediated signaling. For example, transient activation of endothelial PI3K/Akt signaling inhibits the expression of adhesion molecules involved in leukocyte rolling and adhesion to the vascular luminal wall.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15, 16 ECs of inflamed adipose tissue from obese subjects have adverse effects on insulin signaling in adipocytes such as reduced expression of phospho-Akt at Ser473, increased endoplasmic reticulum stress, and release of inflammatory mediators. 17 On the other hand, EC function is subjected to the regulation by insulin-mediated signaling. For example, transient activation of endothelial PI3K/Akt signaling inhibits the expression of adhesion molecules involved in leukocyte rolling and adhesion to the vascular luminal wall.…”
Section: Introductionmentioning
confidence: 99%
“…19, 20 Indeed, ECs from visceral adipose tissue of obese mice or human subjects exhibit a marked inflammatory state with increased expression of chemokines, cytokines, and adhesion molecules. 17, 21 Several studies have shown insulin signaling in ECs protect endothelial function and attenuates the progression of atherosclerosis. 2225 However, it remains unknown whether enhancing endothelial insulin signaling in adipose tissue may improve systemic insulin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…We tested the role of the two proinflammatory cytokines IL-6 and IL-1b as drivers of myotube inflammation observed in cocultures based on previous reports (26,33,34). After 3 days of culture, in the presence of the neutralizing IL-6/IL-1b antibodies, the inflammatory response of cocultured cells was reduced with decreased levels of G-CSF (271.4%); fractalkine (258%); IL-7 (256%); and the chemokines CXCL1/2/3 (253%), CCL7 (242%), IL-8 (243.5%), interferon-g-induced protein-10 (236%), and CCL5 (238%) (Fig.…”
Section: Il-6 and Il-1b Have A Relevant Role In Inflammation Of Myotumentioning
confidence: 99%
“…Mature adipocytes and muscle cells were then embedded in separate hydrogels (Supplementary Fig. 2A and B), which were previously characterized by the ability to maintain altered functions of obese adipocytes (26). Direct cocultures of human cells in a 3D setting are of great value because they allow the study of a complex set from adipocyte-derived signals that regulate skeletal muscle functions without confounding the effects of other organ systems, while maintaining signals including labile diffusible factors.…”
Section: Vat Adipocytes Directly Induce Muscle Cell Atrophy In a 3d Smentioning
confidence: 99%
See 1 more Smart Citation